Colour and Fastness of Fabrics Dyed with Walnut (Juglans regia L.) Base Natural Dyes - Tutak, Mustafa; Benli, Huseyin (Asian Journal of Chemistry, 2010)
Turkey has a great number of walnut trees which include nutritious components. However, only the inside part of walnut is used as a nutrient while the rest of it is waste. This study suggests that the waste parts of the walnut could be used as a natural dye for dyeing textile fibres. The dyeing properties of leaves, husk and shell of the walnut were examined on various textile fibres (wool, cotton and viscose) by using different metal salts. Mordants used in dyeing process were choosen as potassium dichoromate, copper sulphate, iron sulphate and alumunium sulphate. Colour performance and fastness properties were investigated after dyeing process. The experimental results indicate that walnut based products can be used in textile dyeing as natural dyes.